2017
DOI: 10.4103/jnrp.jnrp_53_17
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Functional Outcomes following Inpatient Rehabilitation in Patients with Acquired Brain Injury: A Prospective Follow-up Study

Abstract: Objectives:To study the effects of cognitive retraining and inpatient rehabilitation to study the effects of cognitive retraining and inpatient rehabilitation in patients with acquired brain injury (ABI).Design and Setting:This was a prospective follow-up study in a neurological rehabilitation department of quaternary research hospital.Patients and Methods:Thirty patients with ABI, mean age 36.43 years (standard deviation [SD] 12.6, range 18–60), mean duration of illness 77.87 days (SD 91.78, range 21–300 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
(35 reference statements)
0
7
0
2
Order By: Relevance
“…A survey by Koh et al (2008) found a particularly high prev-alence of MMSE in Australia, and a different study reported it to be the most frequently mentioned assessment among clinicians in Canada [11]. A high prevalence of MMSE and MoCA assessments was also found in other studies [11,21]. The aims of the MMSE and MoCA approaches are comparable as both are routine cognitive screening tests rated on a 30point scale that attempt to detect mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 93%
“…A survey by Koh et al (2008) found a particularly high prev-alence of MMSE in Australia, and a different study reported it to be the most frequently mentioned assessment among clinicians in Canada [11]. A high prevalence of MMSE and MoCA assessments was also found in other studies [11,21]. The aims of the MMSE and MoCA approaches are comparable as both are routine cognitive screening tests rated on a 30point scale that attempt to detect mild cognitive impairment.…”
Section: Discussionmentioning
confidence: 93%
“…It can be used in patients who are intubated and can be used to recognize locked-in syndrome. FIM-COG™ Scale 26 The FIM scale is a clinical tool with 7 sections that is used to determine the level of assistance a patient requires to complete activities of daily living. The FIM-COG™ is a subscale of the FIM scale, which focuses on social cognition and communication.…”
Section: Appendix Amentioning
confidence: 99%
“…Acquired brain injury (ABI), including traumatic brain injury (TBI) and stroke, is the leading cause of disability worldwide [1][2][3]. According to the World Health Organization, the global incidence of all-severity TBI is estimated at 69 million people, while 15 million people suffer a stroke worldwide each year [4][5][6].…”
Section: Introductionmentioning
confidence: 99%